Percussionist-Centred Design for Touchscreen Digital Musical Instruments. - Martin, Charles P. (Contemporary Music Review)
This article describes how percussive interaction informed the design, development, and deployment of a series of touchscreen digital musical instruments for ensembles. Percussion has previously been defined by techniques for exploring and interacting with instruments, rather than by the instruments themselves. Percussionists routinely co-opt unusual objects as instruments or create them from scratch. In this article, this process is used for the iterative design and evaluation of five mobile music apps by percussion ensembles. The groups helped refine the apps from prototype to performance through research rehearsals where they improvised, explored new musical gestures, and collaborated to develop practical performance strategies. As a result, the affordances and limitations of the apps were discovered, as were a vocabulary of percussive touch gestures. This article argues that this percussionist-centred process was an effective method for developing musical apps, and that it could be applied more widely in designing musical computer systems.